PENERAPAN GOOD MANUFACTURING PRACTICES(GMP) DAN SANITATION STANDARD OPERATING PROCEDURE(SSOP) PADA PRODUK BAKSO IKAN BANDENG (Chanos chanos) DI PT INDO LAUTAN MAKMUR SIDOARJO JAWA TIMUR - Basri Basri; Andiki Yelofeva (SEMAH Jurnal Pengelolaan Sumberdaya Perairan, 2022)
The purpose of research is to find out firsthand how to apply GMP and SSOP to milkfish meatball products at PT Indo Samudra Prosperous, Knowing the percentage level of application good manufacturing practices (SSOP) and sanitation standard operating procedure (SSOP). The conclusion of observations at PT Indo Lautan Makmur, Sidoarjo, East Java regarding the suitability of the application of GMP in the processing of milkfish meatballs has an average value of 93.78%. These results show a rating scale of 90%-94.9% which is very good. This shows that PT Indo Lautan Makmur has implemented the principles of Good Manufacturing Practices (GMP) in accordance with the applicable regulations. However, there are some things that need to be improved on the scope of sanitation facilities and programs, especially at the point of location and environment as well as the implementation of a sanitation program where PT Indo Lautan prosperous is located close to residential areas and employees who do not put masks on properly when packing and also talk when do the packing. Overall, the suitability of the application of GMP at PT Indo Samudera prosperous is in accordance with GMP at UPI according to SNI. On the suitability of the SSOP at PT Indo Lautan Makmur it is appropriate because it has an average percentage of 94.12%. These results show a rating scale of 90% -94.9% which is very good. This shows that PT Indo Lautan Makmur has implemented the principles of Sanitation Standard Operation Procedure (SSOP) well. However, there is something that needs to be improved and evaluated again on the protection of materials from harmful contamination because the percentage of weight is 91%.